Enhancing Economic Empowerment: Program Strategy and Impact of Productive Zakat for Beneficiaries at LAZISMU DIY - Sutrisno (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to examine the program strategy and impact of productive zakat in enhancing the economic empowerment of beneficiaries at LAZISMU Special Region of Yogyakarta (DIY). Productive zakat serves as a strategic instrument of Islamic social finance designed not only to provide temporary assistance but also to strengthen the economic capacity of beneficiaries through sustainable income-generating activities. This research employed a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation involving LAZISMU DIY management and beneficiaries of productive zakat programs. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the productive zakat strategy at LAZISMU DIY is implemented through several stages, including beneficiary identification, business feasibility assessment, provision of business capital, mentoring, entrepreneurship training, and periodic monitoring and evaluation. The program mainly targets micro-enterprise sectors such as trade, culinary businesses, agriculture, and services. The impact of the program demonstrates significant improvements in beneficiaries’ income, business productivity, entrepreneurial capacity, and financial independence. Furthermore, the program contributes to reducing dependence on consumptive aid and encourages long-term self-reliance. However, challenges remain, including limited capital allocation, low business literacy among some beneficiaries, and market uncertainty. This study concludes that productive zakat can effectively enhance economic empowerment when supported by integrated strategies involving financial assistance, continuous mentoring, and sustainable program evaluation.